Mindfulness for Children and Youth: A Review of the Literature with an Argument for School-Based Implementation - Rempel, Kim (Canadian Journal of Counselling and Psychotherapy, 2012)
Interest in the use of mindfulness-based activities with children and youth is growing. The article evaluates empirical evidence related to the use of mindfulness-based activities to facilitate enhanced student learning and to support students’ psychological, physiological, and social development. It also provides an overview of interventions that include mindfulness. There is a need to provide children with a way to combat the stress and pressure of living in today’s highly charged world: mindfulness may be one helpful alternative. The implications of a universal school-based mindfulness intervention are discussed, and directions for future research are offered.